2021
DOI: 10.1177/08258597211036243
|View full text |Cite
|
Sign up to set email alerts
|

End of Life Care Practices for Hindu Patients During COVID-19

Abstract: With coronavirus disease 2019, the risk of death has increased in the general population. In these unprecedented times and even otherwise, it is important for the health care professionals caring for Hindu patients to be aware of the end of life practices in Hinduism. There is limited information in the medical literature about traditions and practices followed in Hinduism which is observed by 15% of the world population. Hinduism is currently the third largest religion following Christianity and Islam. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…In general, there is an increasing call for appropriate advance care planning education materials across cultures. 39,40 Deaf clubs provide community connections and offer opportunities to distribute resources related to health care. 41 Participants valued clinicians involved in Deaf community spaces, which once again demonstrated the need for culturally relevant Deaf health education.…”
Section: Discussionmentioning
confidence: 99%
“…In general, there is an increasing call for appropriate advance care planning education materials across cultures. 39,40 Deaf clubs provide community connections and offer opportunities to distribute resources related to health care. 41 Participants valued clinicians involved in Deaf community spaces, which once again demonstrated the need for culturally relevant Deaf health education.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, when discussing treatment options with Buddhists or Hindus, understanding of the life cycle, karma, and samsara—the belief that their actions in past lives predetermine their current physical suffering—is necessary. 19 , 20 Patients with such beliefs might consider that undergoing physical suffering at EOL could reverse negative karma and mean that the departing soul will experience less suffering in the next life. 19 In such instances, symptom relief should be offered while being open to accommodating a patient's wish to not pursue symptom management.…”
Section: Cultural Considerations In Asiamentioning
confidence: 99%
“… 19 , 20 Patients with such beliefs might consider that undergoing physical suffering at EOL could reverse negative karma and mean that the departing soul will experience less suffering in the next life. 19 In such instances, symptom relief should be offered while being open to accommodating a patient's wish to not pursue symptom management. Studies have shown that, besides involving religious leaders or interpreters, religious terms are also helpful in addressing medically obscure concepts, such as using the term mudharat (or harm in Islam) when discussing medical futility.…”
Section: Cultural Considerations In Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…This religion originated in ancient India and is distinguished by a diverse set of beliefs, practices, and rituals (Sengupta, 2021). Despite its complexity, Hinduism is united by a shared set of core beliefs, such as reincarnation, the existence of multiple gods and goddesses, and the ultimate goal of liberation from the cycle of rebirth (Chandratre and Soman, 2022). Hinduism has adapted and evolved in response to changing social and cultural conditions, developing new practices and interpretations of the faith while preserving its core beliefs and traditions.…”
Section: Introductionmentioning
confidence: 99%